2015
DOI: 10.2147/agg.s55776
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and epigenetics of eating disorders

Abstract: Eating disorders (EDs) are serious psychiatric conditions influenced by biological, psychological, and sociocultural factors. A better understanding of the genetics of these complex traits and the development of more sophisticated molecular biology tools have advanced our understanding of the etiology of EDs. The aim of this review is to critically evaluate the literature on the genetic research conducted on three major EDs: anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED). We will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 259 publications
(245 reference statements)
1
100
2
Order By: Relevance
“…Genetic explanations focus on the biological mechanisms behind AN. Family, twin, and genetic studies found that AN runs in families [46]. A family history of AN puts people fourfold more at risk and relatives of women diagnosed with AN are 11 times more at risk of developing AN than controls [47,48].…”
Section: Genetic Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic explanations focus on the biological mechanisms behind AN. Family, twin, and genetic studies found that AN runs in families [46]. A family history of AN puts people fourfold more at risk and relatives of women diagnosed with AN are 11 times more at risk of developing AN than controls [47,48].…”
Section: Genetic Explanationsmentioning
confidence: 99%
“…For example, people with a diagnosis of AN have a higher risk of developing OCD or vice versa [50]. Thus, genetic factors are considered responsible for 48-74% of the total variance in liability to AN [46]. Nevertheless, genetic factors cannot alone predict who will develop AN, as most of the cases do not have a familial history of EDs.…”
Section: Genetic Explanationsmentioning
confidence: 99%
“…1 Recent advances in technology and the decreased cost of genomic experiments now allow for millions of loci to be examined simultaneously in large numbers of individuals through methods such as genome-wide association studies (GWAS) and high-throughput exome and whole-genome sequencing. Here we summarize recent eating disorders genetic research with a genome-wide focus.…”
Section: Recent Insights From Molecular Genetic Studiesmentioning
confidence: 99%
“…Replicated heritability estimates for AN range between 0.48 and 0.74; for BN, between 0.55 and 0.62, and for BED, between 0.39 and 0.45. 1 Although all of these studies have been conducted on European-ancestry populations, results have converged to support the role of genetic factors in the etiology of these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence suggest a notable genetic component in the etiology of AN. Twin studies have estimated the heritability ( h 2 ) of AN to be 0.5-0.6 (Bulik et al , 2006, Yilmaz et al , 2015), and genomic efforts are underway to elucidate the role of genome-wide common variation in the etiology of AN (Boraska et al , 2014, Wang et al , 2011, Duncan et al , 2016). Considering the important role copy number variants (CNVs) play in psychiatric phenotypes (Bergen et al , 2012, Cooper et al , 2011, International Schizophrenia, 2008, Levinson et al , 2011, Malhotra and Sebat, 2012, Sanders et al , 2011, Szatkiewicz et al , 2014), studies are needed to help elucidate their role in AN.…”
Section: Introductionmentioning
confidence: 99%